Liver transplantation in Japan: Registry by the Japanese Liver Transplantation Society - Umeshita, Koji; Eguchi, Susumu; Egawa, Hiroto; Haga, Hironori; Kasahara, Mureo; Kokudo, Norihiro; Sakisaka, Shotaro; Takada, Yasutsugu; Tanaka, Eiji; Eguchi, Hidetoshi; Uemoto, Shinji; Ohdan, Hideki (Hepatology research, 2019)
As of 31 December 2017, a total of 9242 liver transplants have been carried out in 67 institutions in Japan. There were 447 deceased donor transplants (444 from heart‐beating donors and 3 from non‐heart‐beating donors) and 8795 living‐donor transplants. The annual total of liver transplants in 2017 was 416 (69 deceased donor transplants and 347 living‐donor transplants). The most frequent indication was cholestatic disease, followed by neoplastic disease and hepatocellular disease. In terms of hepatocellular disease in 2017, cirrhosis due to hepatitis C and B decreased (13 and 8, respectively), whereas alcoholic cirrhosis markedly increased (32). Patient survival following transplantation from heart‐beating donor (444 transplants: 1 year, 89.1%; 3 years, 85.2%; 5 years, 82.9%; 10 years, 75.4%; 15 years, 70.7%) was similar to that from living‐donor (8794 transplants: 1 year, 85.0%; 3 years, 80.9%; 5 years, 78.5%; 10 years, 73.2%; 15 years, 68.5%; 20 years, 65.7%; 25 years, 64.6%). Graft survival was very much the same as patient survival (heart‐beating donor: 1 year, 88.4%; 3 years, 84.5%; 5 years, 82.2%; 10 years, 74.7%; 15 years, 70.1%; living donor: 1 year, 84.3%; 3 years, 79.9%; 5 years, 77.3%; 10 years, 71.4%; 15 years, 66.3%; 20 years, 63.3%; 25 years, 61.9%). Survival data are reported according to age and sex of recipient, indication, age and sex of donor, ABO compatibility, and other factors.